Penerapan Model Altman Z-Score Dalam Memprediksi Potensi Kebangkrutan Perusahaan Sub Sektor Otomotif dan Komponen Pada Bursa Efek Indonesia - Veron Vebrianty Soputan, Jesyca (Jurnal Indonesia Sosial Sains, 2022)
The failure of a company from external factors that affect the company's condition as happened in 2020, the largest decline occurred because Indonesia was hit by the corona virus outbreak (COVID-19) which had a negative impact on the economy, including the growth of the domestic automotive market. The demand for the product decreased, and the production process of the producers was disrupted and even suffered losses. Analysis of the company's financial statements is very important to minimize the risk of company bankruptcy. The potential for bankruptcy can be identified early using a predictive model that can provide early warning for companies formulated by several experts, one of which is the Altman Z-Score. This study aims to determine the results of bankruptcy analysis in automotive sub-sector manufacturing companies and their components listed on the Indonesia Stock Exchange in 2016-2020 with the Altman Z-Score prediction model. The type of research used is descriptive quantitative research. This study uses secondary data from 12 company financial statements with modified Altman Z-Score model analysis techniques. The results of research conducted on 12 automotive and component sub-sector companies listed on the Indonesia Stock Exchange in 2016-2020 using the Altman Z-Score research model on average show that the 12 companies studied are in the safe zone.